Investigating a hyper-endemic focus of Taenia solium in northern Lao PDR - Okello, A.; Ash, Andrew J.; Keokhamphet, C.; Hobbs, E.; Khamlome, Boualam; Dorny, P.; Thomas, Lian F.; Allen, J. (Springer, 2014)
Background The Taenia solium cysticercosis-taeniasis complex is a Neglected Tropical Disease of significant public health importance in many impoverished communities worldwide. The parasite is suspected to be endemic in Lao PDR as a result of widespread risk factors including open human defecation, free ranging pigs and weak systems for meat inspection and carcass condemnation. Reported prevalences of human taeniasis throughout the country have ranged from 0-14%, although few of these have definitively diagnosed T. solium, grossly indistinguishable from Taenia saginata (beef tapeworm) and Taenia asiatica. This short communication details the suspicion of a hyper endemic "hotspot" of T. solium in a remote Tai Dam village in northern Lao PDR. Findings: Initial antibody serosurveillance of four provinces in Lao PDR in 2011 indicated human taeniasis and cysticercosis prevalences of 46.7% and 66.7% respectively, in the village of Om Phalong in the north of the country. Subsequent copro-antigen ELISA on 92 human faecal samples from this same village, representing a total 27.9% of the target community, indicated a taeniasis prevalence of 26.1% (95% CI = 18.2-35.9). Subsequent PCR and sequencing of samples (n = 5) all identified as T. solium; the other human tapeworms T. saginata and T. asiatica were not detected in any of the samples genotyped. Conclusion This is potentially one of the highest documented prevalences of T. solium taeniasis to date in Lao PDR, if not the Southeast Asia region. This result raises suspicion that other "hotspots" of T. solium hyper endemicity may exist in the region, particularly in communities where the consumption of raw pork is commonplace as a result of cultural practices.